Long‐term redevelopment of resource islands in shrublands of the Great Basin, USA. Issue 1 (21st January 2013) - Morris, Lesley R.; Monaco, Thomas A.; Blank, Robert; Sheley, Roger L.
Abstract : Soil resource availability in semi‐arid and arid shrubland ecosystems is highly heterogeneous and includes patterns of accumulation primarily beneath shrubs as opposed to shrub interspaces. These resource islands contribute to ecosystem resilience after natural disturbances such as fire, yet very little is known regarding their redevelopment following soil disturbance and shrub re‐colonization. Cultivation involves the removal of native vegetation and mixing of soils both vertically and horizontally. The old fields in this study offered a unique look at the long‐term redevelopment of resource islands under shrubs where cultivation was abandoned nearly a century ago. Using adjacent pairs of previously cultivated and native shrubland from three soil series, we sampled surface soils (0–5 cm) in microsites under shrubs and in the interspaces between them to examine if the soil fertility in old fields (C, N, P, Ca, Mg, K) had regained similar microsite patchiness to the native shrubland, if the values of each soil fertility measure in old fields were different from native shrubland, and if the overall microsite fertility under shrubs in old fields was different from non‐disturbed microsites. We found that while most of the resource island patterning had redeveloped, the content of each fertility measure had not recovered to pre‐disturbance levels. Further, the recovery was different between the soil series and between sites with different dominant shrub species. There were also differences between sites within the same soil series, suggesting that historical cultivation practices may influence resource island recovery in multiple ways. Overall, under‐shrub microsite fertility in previously cultivated areas was distinct from comparable under‐shrub microsites in native areas in two out of the three soil series. These findings suggest that while patterning may redevelop within 90 years, it may take over a century for resource island fertility to fully re‐establish in some formerly cultivated soils.